MENCERMATI PENGARUH UTANG DAN VARIABEL MAKROEKONOMI TERHADAP SUSTAINABILITAS FISKAL DI INDONESIA - Pertiwi, Intan Puspaning; Camalia, Nur Dina; Rega, Raina; Kartiasih, Fitri (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
Expansive fiscal policy causes government expenditure to accelerate faster than its revenue. Debt is the most common alternative used by a country in financing a budget deficit. Fiscal policy is said to be sustainable if the government is able to manage its debt and financing so that it does not burden the budget in the future. This study aims to determine the effect of debt and macroeconomic variables on fiscal sustainability in Indonesia in 1986-2020. The data used is secondary data in the form of time series obtained from the APBN, IMF, the Ministry of Finance, and The World Bank. This research uses Vector Error Correction Model (VECM) analysis method. The conclusion of this study shows that in the long term, the government is less able to respond to the increase in debt burden so that fiscal policy in the 1990-2021 period is not sustainable. In addition, debt ratios, oil prices, economic growth, and interest rates each have a significant effect on the primary balance ratio. Meanwhile, the exchange rate has no significant effect on the primary balance ratio.